KEDUDUKAN REKAMAN CLOSED CIRCUIT TELEVISION SEBAGAI ALAT BUKTI TINDAK PIDANA UMUM BERDASARKAN PASAL 184 KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Mieke Christian S; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
This study examines and answer legal issues regarding the position of Close Circuit Television (CCTV) in the proof at trial a general criminal offense under article 184 the Code of Criminal Procedure which governs the five legal evidence.In this study the authors use the method of normative-juridical research is the search for truth is coherence in addressing issues in the law through the study of law is intrinsically (legal research), with the approach of the Act (statute approa ch) and the conceptual approach (conseptual approach). Sources of research used in the form of primary legal materials namely Law No. 8 of 1981 About the Book of Criminal Procedure Law, and Law Number 11 Year 2008 on Transaction and Electronic information, as for secondary law material refers to reference books as well Legal journals. Once the legal material is classified secra systematically then analyzed to draw conclusions and provide prescription.The results showed that Close Circuit Television (CCTV) conducted in the framework of law enforcement at the request of the police, prosecutors and / or other law enforcement institutions established under the law as explicitly stated in the Constitutional Court Decision Number 20 / PUU-XVI / 2016 Valid evidence that may be used to obtain the judge's conviction in the trial of a general criminal offense, for as information stored electronically, the CCTV record shall be a valid evidence as provided for in Act Number 11 of 2008 on Information and Electronic Transactions, By using systematic method of interpretation and holding on to the organic view that the whole legislation as a whole system, the CCTV record as electronic evidence is an extension of evidences as set forth in Article 184 of the Criminal Procedure Code whose application is not limited to criminal acts Specific, but also applicable in the evidence of a general criminal trial.Key Word : CCTV Recording, Evidence, Proof Of General Crime